Selective boron delivery to murine tumors by lipophilic species incorporated in the membranes of unilamellar liposomes. - Feakes, D A (1995)
The nido-carborane species K[nido-7-CH3(CH2)15-7,8-C2B9H11] has been synthesized for use as an addend for the bilayer membrane of liposomes. Small unilamellar vesicles, composed of distearoylphosphatidylcholine/cholesterol, 1:1, and incorporating K[nido-7-CH3(CH2)15-7,8-C2B9H11] in the bilayer, have been investigated in vivo. The time-course biodistribution of boron delivered by these liposomes was determined by inductively coupled plasma-atomic emission spectroscopy analyses after the injection of liposomal suspensions in BALB/c mice bearing EMT6 mammary adenocarcinomas. At the low injected doses normally used (approximately 5-10 mg of boron per kg of body weight), peak tumor boron concentrations of approximately 35 micrograms of boron per g of tissue and tumor/blood boron ratios of approximately 8 were achieved. These values are sufficiently high for the successful application of boron neutron capture therapy. The bilayer-embedded boron compound may provide the sole boron source or, alternatively, a concentrated aqueous solution of a hydrophilic boron compound may also be encapsulated within the liposomes to provide a dose enhancement. Thus, the incorporation of both K[nido-7-CH3(CH2)15-7,8-C2B9H11] and the hydrophilic species, Na3[1-(2'-B10H9)-2-NH3B10H8], within the same liposomes demonstrated significantly enhanced biodistribution characteristics, exemplified by maximum tumor boron concentrations of approximately 50 micrograms of boron per g of tissue and tumor/blood boron ratios of approximately 6.